Lotus Land - Poelgeest, Darcy van (BOOM! Studios, 2024)
"Is entropy the end, or is there another way? The mysterious Keeper Program in a cyberpunk, decaying Vancouver of the near-future has developed highly-advanced technology that calls this into question, playing god with the meaning of human life itself. But when an attack on the clandestine program occurs, former police detective Bennie Strikman comes out of retirement to take on one final, chilling case, and hopefully take those involved with the program out of harm's way. But the secrets of the Keeper Program grow deep, with the heart of everything directly connected to the chilling trail that Bennie follows. He won't be the same after what he uncovers... Eisner-winning and Harvey-nominated writer and director Darcy Van Poelgeest (Little Bird) is joined by rising star artist Caio Filipe (Stranger Things: Tales From Hawkins) for this timely and thought-provoking look into the human condition, set in a dystopia that's as grounded as it is metaphysical"--Amazon.